2009
DOI: 10.1523/jneurosci.5865-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Increases Brain Levels of Ferritin Heavy Chain Leading to Inhibition of CXCR4-Mediated Survival Signaling in Neurons

Abstract: This study focuses on the effect of -opioid receptor agonists on CXCR4 signaling in neurons and the mechanisms involved in regulation of neuronal CXCR4 by opiates. The data show that CXCR4 is negatively modulated by long-term morphine treatments both in vitro and in vivo; CXCR4 inhibition is caused by direct stimulation of -opioid receptors in neurons, leading to alterations of ligand-induced CXCR4 phosphorylation and upregulation of protein ferritin heavy chain (FHC), a negative intracellular regulator of CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
117
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(136 citation statements)
references
References 68 publications
11
117
1
6
Order By: Relevance
“…The increased capacity to sequester iron is an efficient protective mechanism against cellular stress, as shown by the block of the TNF-/JNK mediated apoptosis obtained through the NF-kb-dependent activation of ferritin transcription (Pham et al 2004). Other pathways of regulation suggest the possible association of ferritin with alternative, cell specific functions (see below); adiponectin can increase ferritin expression in primary skeletal muscle cells by recruitment of NF-kb (Ikegami et al 2009) while in neurons a transcription-dependent increase of ferritin H is observed upon the activation of -opiod receptors (Sengupta et al 2009). A strong post-transcriptional regulation of ferritin is superimposed to the transcriptional one to guarantee rapid adaptations to changes in iron levels and oxidative stress.…”
Section: Regulation Of Ferritin Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased capacity to sequester iron is an efficient protective mechanism against cellular stress, as shown by the block of the TNF-/JNK mediated apoptosis obtained through the NF-kb-dependent activation of ferritin transcription (Pham et al 2004). Other pathways of regulation suggest the possible association of ferritin with alternative, cell specific functions (see below); adiponectin can increase ferritin expression in primary skeletal muscle cells by recruitment of NF-kb (Ikegami et al 2009) while in neurons a transcription-dependent increase of ferritin H is observed upon the activation of -opiod receptors (Sengupta et al 2009). A strong post-transcriptional regulation of ferritin is superimposed to the transcriptional one to guarantee rapid adaptations to changes in iron levels and oxidative stress.…”
Section: Regulation Of Ferritin Expressionmentioning
confidence: 99%
“…Stimulation of CXCR4 by its ligand CXCL12 induces FtH phosphorilation at serine 178 and subsequent translocation to the nucleus. The discovery that opioids induce new synthesis of FtH can explain the heterologous desensitization observed between -opioid receptors (MOR) and CXCR4 in neurons (Sengupta et al 2009), a possible mechanism underlining the neurological dysfunction and cerebral damage determined by opiates. This activity is independent of iron binding since it is maintained by a ferroxidase deficient FtH (Pitcher et al 2014).…”
Section: Mammalian Cytosolic Ferritin Not Only Ironmentioning
confidence: 99%
“…Recently, our group has shown that morphine (and selective μ-opioid receptor [MOR] agonists, such as DAMGO) specifically impairs CXCL12/CXCR4 signaling in neurons, both in vitro and in vivo, by increasing protein levels of ferritin heavy chain (FHC), a recently described CXCR4 regulator (25,(27)(28)(29). Morphine increases the level of FHC and its association with CXCR4, thereby inhibiting CXCR4 activation and downstream prosurvival signaling pathways (27).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has shown that morphine (and selective μ-opioid receptor [MOR] agonists, such as DAMGO) specifically impairs CXCL12/CXCR4 signaling in neurons, both in vitro and in vivo, by increasing protein levels of ferritin heavy chain (FHC), a recently described CXCR4 regulator (25,(27)(28)(29). Morphine increases the level of FHC and its association with CXCR4, thereby inhibiting CXCR4 activation and downstream prosurvival signaling pathways (27). This novel CXCR4-regulatory function of FHC occurs seemingly independent from the protein's primary role as a critical regulator of intracellular iron levels; in this context, FHC functions by binding, oxidizing, and sequestering free reactive iron, which is stably stored within the ferritin complex formed by FHC and its partner subunit, ferritin light chain (FLC).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, glia contamination in the neuronal layer is prevented by different means (low density culture, addition of mitotic inhibitors, lack of serum and use of optimized culture medium) leading to a virtually pure neuronal layer, comparable to other established methods [1][2][3] . Neurons can be easily separated from the glial layer at any time during culture and used for different experimental applications ranging from electrophysiology 4 , cellular and molecular biology 5-8 , biochemistry 5 , imaging and microscopy 4,6,7,9,10 .…”
Section: Introductionmentioning
confidence: 99%